Core Reflection as a Way Towards Integrating Theoretical Knowledge and Pedagogical Practice in the Iranian Context: The Case of Prospective Language Teachers - Bahareh Khazaeenezhad (Teaching English Language, 2018)
This study was an attempt to examine the levels of teacher activity and reflection phases Iranian prospective language teachers go through in a way to put into practice the concepts and theories explored on campus within their workplace. To this end, Core Reflection Model was practiced by drawing on reflective journals, focus group discussions, and field notes collected over a four month period. The findings indicated that reflections on all six levels of the core reflection model took place mostly being on the level of convictions or beliefs, followed by competencies, behavior, environment, identity, and mission. Moreover, through the movement of reflection among the five phases, a shift from the second phase, looking back at action, to the third one, awareness of essential aspects, was observed and held on to the last phase; the reason could be the lack of mentorship and supervisory interventions for promoting guided reflection practice for prospective teachers in English language teacher education in Iran. In general, utilizing core reflection model in language teacher education for prospective teachers seems to be successful, because the model fostered the reflection of language teachers on all levels and phases and could empower them in their practice.